Differentiation with SEM of six species of Meloidogyne (Nemata: Heteroderidae) found in Costa Rica - López Chaves, Róger (1994)
The morphology of one isolate each of Meloidogyne incognita, M.javanica, M. hapla, M. exigua, M. salasi, and M. arabicida, from Costa Rica was studied with the scanning electron microscope. Good characteristics for the differentiation of the six species were found in the labial and cephalic regions of females, males, and second-stage juveniles, but the single most reliable morphological character was the female perineal pattern.